The electron temperature in the plasma of a spark-recombination laser - Villagran, M., author; Tocho, J. O., author; Gallardo, M., author; Rocca, Jorge J., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1987)
The electron temperature in an expanding spark plasma used as active medium in a cadmium recombination laser was measured using the relative intensities of helium lines originated from levels in local thermodynamic equilibrium. Measurements resolved in space and time show that the electron temperature at the conditions of maximum gain are 1000 and 600 K at 5 and 10 mm of the sparks, respectively. Rapid cooling occurs after the termination of the discharge-current pulse, and the electron temperature reaches values below 1000 K. Subsequently, the electron temperature decrease is slow. The optical gain calculated for the 1.43-μm Cd (I)-recombination-laser transition using the measured electron temperature and particle density values is 3 × 10-3 cm-1, in good agreement with measurements.